The moral witness : trials and testimony after genocide - Dean, Carolyn J. 1960- (Corpus juris : the humanities in politics and law, 2019)
"The Moral Witness maps the emergence of a 'witness to genocide' over a century, from its origins in interwar court trials to the Jewish Holocaust survivor and to today's global witness, who represents new obligations to suffering humanity at home and abroad"--